Diffuse interstellar bands towards ο Per and ξ Per - Debudej, A.; Kusiak, S.; Ozga, J.; Wszołek, B. (Advances in Astronomy and Space Physics, 2012)
Spectroscopic characteristics of interstellar matter vary strongly with the direction to the target star. Spectra of oPer and ξ Per contain many prominent and weak diffuse interstellar bands as well as absorption lines of some identiffed interstellar atoms and molecules. Using echelle optical spectra of these bright and moderately reddened stars we selected well detectable diffuse interstellar bands (DIBs). We measured intensities of all well noticeable absorption features to compare them with their counterparts observed in spectra of the other target stars.